In hostile skies : an American B-24 pilot in World War II - Davis, James M., 1921- (North Texas military biography and memoir series, 2006)
James "Jim" Davis lived what he considered "an impossible dream" as he piloted a B-24 as part of the 8th Air Force on more than thirty missions in the European Theatre during World War II. He flew support missions for Operations Cobra and Market Garden and numerous bombing missions over occupied Europe in the summer and fall of 1944